Gender stereotypes in the folktales and proverbs of the Baganda - Kiyimba, Abasi (Kampala, 2001)
Theses (Ph.D, Literature) - Makerere University, 2001
Includes bibliographical references (p. 263-281)
Keywords: Gender identity in literature; Tales -- Buganda; Proverbs, Ganda